Influence of Safety Management Practices on Safety Performance with Safety Knowledge as Intervening Variable in Safety Representative - Rina Sandora; Dewi Kurniasih; Gilang Armanda Putri (Tibuana, 2023)
Phosphoric acid production companies have a lot of potential hazards that can lead to work accidents. The preventive actions taken by the company is by establishing an SHE (Safety, Health and Environment) division and appointing a safety representative. Based on the results of the safety patrol record, it turns out that there are still a lot of unsafe actions and unsafe conditions that occur and the value of the frequency rate in 2021 is worth 0.23. This study aims to determine the influence of safety management practices on safety performance mediated by the safety knowledge on 40 safety representatives. The method used to analyze the relationship between variables is PLS-SEM (Partial Least Square – Structural Equation Modeling). The results showed that there was a positive and significant influence between safety management practices on safety performance with a p-value of 0.018. In addition, safety management practices also have a positive and significant impact on safety performance mediated by safety knowledge with a p-value of 0.004 and a VAF value of 49,59%. Recommendations that can be given are in the form of implementing safety training, installing safety signs in the workplace, updating and socializing standard operating procedures for work and implementing safety talk and safety briefing.